2011
DOI: 10.1021/cm203058p
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Resistant Organic Transistors and Thermally Stable Organic Photovoltaics Based on Cross-linkable Conjugated Polymers

Abstract: Conjugated polymers, in general, are unstable when exposed to air, solvent, or thermal treatment, and these challenges limit their practical applications. Therefore, it is of great importance to develop new materials or methodologies that can enable organic electronics with air stability, solvent resistance, and thermal stability. Herein, we have developed a simple but powerful approach to achieve solvent-resistant and thermally stable organic electronic devices with a remarkably improved air stability, by int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 161 publications
(124 citation statements)
references
References 42 publications
4
120
0
Order By: Relevance
“…In addition, the (010) reflection peaks from the π-π stacking of P3HTs in two different active layers appeared in both in-plane (edge-on) and out-of-plane (face-on) directions, which is commonly observed in previous works [45,46]. The π-π stacking distance (010) of P3HT in both BCBCBA and bis-PCBM mixed film was calculated to be 0.38 nm (q z ¼1.65 Å À 1 ) from the out-of-plane plot, consistent with the literature values for well-ordered P3HT crystals [47][48][49]. For quantitative analysis of the crystalline order of P3HT, the crystal size of P3HT in each active layer was calculated using Scherrer equation [48,[50][51][52][53].…”
Section: Resultssupporting
confidence: 88%
“…In addition, the (010) reflection peaks from the π-π stacking of P3HTs in two different active layers appeared in both in-plane (edge-on) and out-of-plane (face-on) directions, which is commonly observed in previous works [45,46]. The π-π stacking distance (010) of P3HT in both BCBCBA and bis-PCBM mixed film was calculated to be 0.38 nm (q z ¼1.65 Å À 1 ) from the out-of-plane plot, consistent with the literature values for well-ordered P3HT crystals [47][48][49]. For quantitative analysis of the crystalline order of P3HT, the crystal size of P3HT in each active layer was calculated using Scherrer equation [48,[50][51][52][53].…”
Section: Resultssupporting
confidence: 88%
“…The parent copolymer and all random copolymers exhibited high thermal stabilities (see Table 1) with decomposition temperatures (5% weight loss = T d ) ranging from 320 to 475°C (RP1, T d = 383°C; RP2, T d = 374°C; and RP3, T d = 344°C; and P1, T d = 355°C). Thus, the synthesized random copolymers are potential candidates for fabricating optoelectronic devices [33,34]. Furthermore, the DSC measurements obtained from the copolymers revealed that P1 and RP1-RP3 were amorphous and did not display noticeable glass transition temperatures (i.e., no melting and no recrystallization points) over the temperature range 30-400°C under a nitrogen atmosphere (see Fig.…”
Section: Thermal Propertiesmentioning
confidence: 93%
“…The photovoltaic performance of single component solar cell of D-A copolymer once again showed higher PCE of 2.46% compared to the random copolymer [110]. Most of the reports on D-A block copolymers employ them as compatibilizer rather than as the active layer component of solar cell, where they are used in small amounts along with P3HT: PC 61 BM blend [111][112][113]. Although covalent linkage of the fullerene with donor polymer blocks did not yield high device efficiencies compared to the blend, latest research in this area highlighted the vital role of the D-A block copolymers in improving the thermal stability of P3HT: PC 61 BM blend solar cell devices by reducing interfacial energy between donor (P3HT) and acceptor (PC 61 BM) which ultimately reduced their phase separation.…”
Section: (B) Fullerene Containing D-a Alternating and Block Copolymersmentioning
confidence: 97%